Development of Corrosion Resistant Welding Technology for Industrial Applications Study on the Impact of Material Variation and Welding Process - Kyaw, Aung Ye (Maritime Park: Journal of Maritime Technology and Society, 2024)
This article discusses the development of stainless welding technology aimed at improving corrosion resistance in industrial applications. The research focuses on the effect of material variation and welding process on the corrosion-resistant performance of welding joints. The research methodology includes the selection of materials with different compositions and the application of various welding techniques. Experiments were conducted to evaluate the microstructure, joint strength, and corrosion resistance properties of the weldments. The results show that material variation has a significant impact on the corrosion resistance of welding joints. The use of certain welding techniques can also affect the corrosion properties of the resulting material. Microstructure analysis provides an in-depth insight into the changes at the microscopic level that affect corrosion resistance. This study makes an important contribution in identifying critical parameters that need to be considered in the development of corrosion resistant welding technology to improve material performance in corrosive industrial environments. In conclusion, a better understanding of the relationship between material and welding process variations and corrosion resistance can help in designing more effective and durable welding technologies for industrial applications. This research has the potential to provide practical guidance for engineers and industry professionals in selecting optimal materials and welding techniques to address corrosion challenges in diverse work environments.